Intimate Partner Violence and Adherence to HIV Pre-exposure Prophylaxis (PrEP) in African Women in HIV Serodiscordant Relationships: A Prospective Cohort Study. (1st November 2016) - Roberts, Sarah T.; Haberer, Jessica; Celum, Connie; Mugo, Nelly; Ware, Norma C.; Cohen, Craig R.; Tappero, Jordan W.; Kiarie, James; Ronald, Allan; Mujugira, Andrew; Tumwesigye, Elioda; Were, Edwin; et al.
Abstract : Background: Intimate partner violence (IPV) is associated with higher HIV incidence, reduced condom use, and poor adherence to antiretroviral therapy and other medications. IPV may also affect adherence to pre-exposure prophylaxis (PrEP). Methods: We analyzed data from 1785 HIV-uninfected women enrolled in a clinical trial of PrEP among African HIV serodiscordant couples. Experience of verbal, physical, or economic IPV was assessed at monthly visits by face-to-face interviews. Low PrEP adherence was defined as clinic-based pill count coverage <80% or plasma tenofovir levels <40 ng/mL. The association between IPV and low adherence was analyzed using generalized estimating equations, adjusting for potential confounders. In-depth interview transcripts were examined to explain how IPV could impact adherence. Results: Sixteen percent of women reported IPV during a median of 34.8 months of follow-up (interquartile range 27.0–35.0). Overall, 7% of visits had pill count coverage <80%, and 32% had plasma tenofovir <40 ng/mL. Women reporting IPV in the past 3 months had increased risk of low adherence by pill count (adjusted risk ratio 1.49, 95% confidence interval: 1.17 to 1.89) and by plasma tenofovir (adjusted risk ratio 1.51, 95% confidence interval: 1.06 to 2.15). Verbal, economic, and physical IPV were all associated with low adherence. However, the impact of IPV diminished and was not statistically significant 3 months after the reported exposure. In qualitative interviews, women identified several ways in which IPV affected adherence, including stress and forgetting, leaving home without pills, and partners throwing pills away. Conclusions: Women who reported recent IPV in the Partners PrEP Study were at increased risk of low PrEP adherence. Strategies to mitigate PrEP nonadherence in the context of IPV should be evaluated.